Do Female Executives Make a Difference? The Impact of Female Leadership on Gender Gaps and Firm Performance. Issue 622 (13th August 2019) - Flabbi, Luca; Macis, Mario; Moro, Andrea; Schivardi, Fabiano
Abstract: We investigate the effects of female executives on gender-specific wage distributions and firm performance. Female leadership has a positive impact at the top of the female wage distribution and a negative impact at the bottom. The impact of female leadership on firm performance increases with the share of female workers. We account for the endogeneity induced by non-random executives' gender by including firm fixed-effects, by generating controls from a two-way fixed-effects regression and by using instruments based on regional trends. The findings are consistent with a model of statistical discrimination in which female executives are better at interpreting signals of productivity from female workers. This suggests substantial costs of women under-representation among executives.